4-Ethyl-1-(4-methylbenzylidene)thiosemicarbazide - Yu-Feng Li; Fang-Fang Jian (Acta Crystallographica Section E, 2010)
In the title compound, C11H15N3S, an intramolecular N—H...N hydrogen bond generates an S(5) ring. In the crystal, inversion dimers linked by pairs of N—H...S bonds occur, generating an R22(8) loop.